Perbandingan Forensic Tools pada Instagram Menggunakan Metode NIST - Irhash Ainur Rafiq; Imam Riadi; Herman (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
The development of communication media continues to increase with the emergence of various communication applications on smartphones, which are currently very developed from limited communication media to social media. This change in the flow of communication applications gives a new color to communication, not just exchanging messages and sounds but also exchanging videos and pictures. This development was also followed by the rise of digital crimes in the form of defamation, fraud, and hoax news by spreading posts and then deleting them after the news spread widely. This research was conducted to obtain digital evidence with the help of special applications such as Belkasoft Evidence and Axiom Magnets using the NIST method. The results of this study show that the Magnet Axiom is better with an accuracy rate of 83.3% while Belkasoft Evidence is only 50%.